Euthanasia in family practice in The Netherlands. Toward a better understanding. - Verhoef, M. J. (College of Family Physicians of Canada, 1997)
OBJECTIVE: To describe the incidence of euthanasia and assisted suicide in family practice in the Netherlands, the reasons for its practice, and the characteristics of patients and physicians involved. DESIGN: Cross-sectional survey of a random sample of Dutch family physicians. SETTING: General practices in The Netherlands. PARTICIPANTS: An anonymous questionnaire was mailed to 1042 general practitioners. Of the 996 eligible physicians, 667 (67%) completed the questionnaire. MAIN OUTCOME MEASURES: Reported practices and beliefs concerning euthanasia and assisted suicide. RESULTS: In the course of an average year, 24% of Dutch family physicians had practised euthanasia or assisted suicide. Most deaths took place at home in the presence of others. According to the physicians, the most important reasons for the request were futile suffering, fear or avoidance of loss of dignity, and unbearable suffering. Euthanasia or assisted suicide was mostly (85%) administered to patients with malignant neoplasms. Physicians were more opposed to euthanasia and assisted suicide if they had never practised it, if they had a religious affiliation, and if they were older. CONCLUSIONS: This study presents empiric data about euthanasia and assisted suicide in the context of a permissive euthanasia policy. Understanding Dutch practices could be helpful for Canadians. However, each country needs to resolve these issues in its own way.